Zwroty grzecznościowe w korespondencji prywatnej na Śląsku Cieszyńskim końca XIX i pierwszej połowy XX wieku - Gaś, Swietłana (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The study presents the results of the analysis of verbal politeness in private letters. The persuasive aspect was taken into account. The paper concentrates on unpublished letters and greeting cards written by inhabitants of Teschen Silesia from the 1894–1952 period. The study shows a local model of politeness. Complying with the rules, the sender of private letters can affect the recipient more efficiently.